Estudio prefactibilidad para la instalación de una planta de producción de bebidas probióticas a base de té de kombucha (Medusomyces gisevi), piña (Ananas comosus) y kion (Zingiber officinale) - Giron Yarasca, Jorge Cesar (2023)
Over the years, people has ben changing their alimentation, lifestyles and ways of thinking. This leads to search a healthy life, careful of what we eat and looking for products that has more benefits and help us with the digestion, for example, probiotic foods or drinks. This study evaluates the market, technical, economic and finantial viability of the installation of production plant for probiotic drinks based on kombucha tea, pineapple and ginger. The main properties of this drink are vitamins, antioxidants and digestive enzymes. The product will be presented en glass bottles of 350 ml, which will be able to maintain the appropiate conditions of the beverage to preserve it. The plant will be located in San Juan de Lurigancho district because of the following factors: closeness to market, proximity to the raw material, landcost, water availability, workforce, transport and energy. The beverage is aimed to people between 18 and 60 years old of NSE A and B of Lima metropolitana. The production plant will have an area of 411.21 m2 and máximum capacity of 459,020.8 kg/hour. The total investment of the project will be S/ 2 297 080 which considers the tangibles and intangible assets, working capital of S/ 523 438. This prooject is profitable because has a positive finantial and economic VAN, economic TIR 38%, a finantial TIR of 70% and B/C ratio higher than the unity and both economic and finantial recovery periodo of less 5 years.